An energy-saving retrofit baseline determination method for large-scale building based on investigation data. (21st April 2019) - Zheng, Donglin; Yu, Lijun; Wang, Lizhen; Tao, Jiangang
Abstract : At present, China is implementing large-scale building energy efficiency retrofit (LSBEER) due to the constraints of total energy consumption and energy use intensity (EUI). It is vital to determine the baseline of LSBEER. There are some limitations to LSBEER in the current baseline methods, such as lack of exhaustive database, mismatching with actual retrofit potential, and inapplicability of physical simulation analysis. This article proposes a baseline determination model to diminish the uncertainty and improve applicability using the example of 100 buildings in Shanghai. The methodology comprises two indexes of EUI and energy saving rate (ESR) including four methods, based on the bilateral match of retrofit target and the practical retrofit potential combined with design standards for public building energy saving. Meanwhile, evaluation indexes are proposed, such as the energy saving potential matching degree (ESPMD) and retrofit building coverage rate (RBCR). Results show that the ESR-based method has an advantage over the other three methods, with the ESPMD and the RBCR reaching 86% and 95%, respectively.